The Legality of the Maluku Governor's Action in Mutating Doctors Between Hospitals - Tanner, Juliani; Salmon, Hendrik; Bakarbessy, Andress Denny (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: There are often problems regarding the mutation of doctors between hospitals in the Maluku Province area carried out by the Governor of Maluku. The action of the Governor of Maluku to carry out the mutation caused a reaction of rejection from the mutated doctors and a number of mutation personnel and members of the Provincial Regional House of Representatives, because it was considered contrary to the provisions of laws and regulations. Purposes of the Research: The purpose of this writing is to analyze the legality of the Maluku Governor's Action of Mutating Doctors Between Regional General Hospitals of Maluku Province, and the Legal Consequences if the Governor of Maluku's Action of Mutating Doctors Between Regional General Hospitals of Maluku Province Does Not Have Legality.Methods of the Research: The research method in this writing is normative legal research. The approaches used in this study are the laws and regulations approach, the conceptual approach, and the case approach.Results Main Findings of the Research: The results of the study show that the Governor of Maluku transfers doctors between hospitals without a basis for authority, because there is no delegation of authority from the President as the holder of the highest power in the development of the State Civil Apparatus. This is evidenced by the absence of Government regulations or Presidential Regulations or Provincial Regulations that regulate the delegation of authority from the President to the Governor of Maluku for the mutation in question. Similarly, mutation is carried out through a mutation procedure for mutation planning for a minimum of 2 (two) years and a maximum of 5 (five) years. Mutation is carried out on the basis of the suitability between the competence of Civil Servants and the requirements of the position, position classification and career pattern, taking into account the needs of the organization, there should be no conflict of interest in the implementation of mutations. For this reason, the mutation of the Governor of Maluku to transfer doctors between hospitals is without authority, and not in accordance with procedures and substance so that it does not have legality, so it has legal consequences in question as invalid. The action of the Governor of Maluku is considered non-binding since it was established and all legal consequences that arise are considered to have never existed, because the mutation carried out by the Governor is null and void for the sake of the law.